Insulin-Like Peptides and Cross-Talk With Other Factors in the Regulation of Insect Metabolism - Chowański, Szymon; Walkowiak-Nowicka, Karolina; Winkiel, Magdalena; Marciniak, Pawel; Urbański, Arkadiusz; Pacholska-Bogalska, Joanna (Frontiers in Physiology, 2021)
The insulin-like peptide (ILP) and insulin-like growth factor (IGF) signalling pathways play a crucial role in the regulation of metabolism, growth and development, fecundity, stress resistance, and lifespan. ILPs are encoded by multigene families that are expressed in nervous and non-nervous organs, including the midgut, salivary glands, and fat body, in a tissue- and stage-specific manner. Thus, more multidirectional and more complex control of insect metabolism can occur. ILPs are not the only factors that regulate metabolism. ILPs interact in many cross-talk interactions of different factors, for example, hormones (peptide and nonpeptide), neurotransmitters and growth factors. These interactions are observed at different levels, and three interactions appear to be the most prominent/significant: 1) confluence of ILPs and other factors on the same target cells, 2) influence of ILPs on synthesis/secretion of other factors regulating metabolism, and 3) regulation of activity of cells producing/secreting ILPs by various factors. For example, brain insulin-producing cells coexpress sulfakinins, which are cholecystokinin-like peptides, another key regulator of metabolism, and express receptors for tachykinin-related peptides, the next peptide hormones involved in the control of metabolism. It was also shown that ILPs in Drosophila melanogaster can directly and indirectly regulate AKH. This review presents an overview of the regulatory role of insulin-like peptides in insect metabolism and how these factors interact with other players involved in its regulation.